1974
DOI: 10.1136/jcp.27.10.767
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical profile of B and T leukaemic lymphocytes with special reference to acute lymphoblastic leukaemia

Abstract: SYNOPSIS The PAS and acid phosphatase reactions showed a different pattern of positivity in the cells of lymphoproliferative disorders according to their B or T cell nature. In B-cell leukaemias (chronic lymphocytic and prolymphocytic) a low proportion of lymphocytes gave a positive result with the acid phosphatase reaction, while the majority were PAS positive in granular form. In contrast, in the T-prolymphocytic and T-lymphoblastic leukaemias the acid phosphatase reaction was positive in the majority of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

1977
1977
1980
1980

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(35 citation statements)
references
References 23 publications
5
30
0
Order By: Relevance
“…The malignant cells formed E rosettes and also had abundant granular reactivity for acid phosphatase and 3-glucuronidase. Comparable enzymatic reactivity has been observed in other T-lymphocyte neoplasms, including Sezary's syndrome (Flandrin & Brouet, 1974) chronic lymphocytic leukaemia of T-cell type and lymphoblastic lymphoma (Catovsky et al, 1974;Stein et al, 1976).…”
Section: Lymphocytic Poorly Differentiatedmentioning
confidence: 83%
See 1 more Smart Citation
“…The malignant cells formed E rosettes and also had abundant granular reactivity for acid phosphatase and 3-glucuronidase. Comparable enzymatic reactivity has been observed in other T-lymphocyte neoplasms, including Sezary's syndrome (Flandrin & Brouet, 1974) chronic lymphocytic leukaemia of T-cell type and lymphoblastic lymphoma (Catovsky et al, 1974;Stein et al, 1976).…”
Section: Lymphocytic Poorly Differentiatedmentioning
confidence: 83%
“…The malignant cells have in particular the surface, cytochemical and biochemical features of immature thymocytes (Kaplan et al, 1974;Gatien et al, 1975;Coccia et al, 1976;Jaffe et al, 1976;Stein et al, 1976;Donlon et al, 1977;Stein & Muller-Hermelink, 1977;Kersey et al, 1978;Kung et al, 1978;Lukes et al, 1978a, b;Bollum, 1979;Long et al, 1979). The marked propensity for progression to leukaemia establishes a continuum between these tumours and a subset of acute lymphoblastic leukaemia (ALL), i.e., the 25% of cases of ALL with T-cell markers (Kersey et al, 1973;Sen & Borella, 1975;Tsukimoto et al, 1976 (Catovsky et al, 1974). In our series of lymphoblastic lymphomas, cases which did not form E rosettes tended to manifest AP activity as a diffuse multigranular reaction.…”
Section: Lymphoblasticmentioning
confidence: 99%
“…In contrast, Brouet et al (1976) could not substantiate an increase of beta-glucuronidase in cells from T-derived acute lymphocytic leukaemia. However, Barr and Perry (1976) (Stein et al, 1972;Catovsky et al, 1974), others have noted a positive PAS reaction in Sezary cells, a T cell proliferation (Taswell and Winkelmann, 1961;Flandrin and Brouet, 1974). In addition, intense PAS reactivity was observed in phytohaemagglutinin stimulated lymphocytes, suggesting the presence of PAS positive material in T cell blasts (Quaglino et al, 1962;Stathopoulos et al, 1974 Brouet et al, 1976) and in the atypical lymphocytes of infectious mononucleosis (Li et al, 1970).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, cytochemical studies in a variety of lymphoproliferative disorders suggested that betaglucuronidase was an enzyme marker for T cells (Flandrin and Brouet, 1974;Flandrin and Daniel, 1974) and periodic-acid Schiff (PAS) a marker for B cells (Astaldi and Verga, 1957;Stein et al, 1972;Catovsky et al, 1974). Some investigators Ritter et al, 1975) suggested that acid phosphatase was a T cell marker in acutelymphocytic leukaemia.…”
mentioning
confidence: 99%
“…These include: male predominance, high leukocyte counts, increased incidence of mediastinal masses, older median age, and a more aggressive course than E-rosette negative surface immunoglobulin negative acute lymphoblastic leukemia (non-T ~O~-B -A L L ) . '~~' Cytochemical studies have shown a characteristic strong focal acid phosphatase activity in the lymphoblasts of most cases of T-ALL.5, 6 Although these clinical and cytochemical features characterize many T-ALLs, it is the opinion of some investiga tors2,3,7*8J8 that there are no cytomorphologic differences between T-ALL and non-T non-B-ALL.…”
mentioning
confidence: 99%